2010
DOI: 10.1111/j.1749-6632.2010.05488.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the natural tetrapeptide acetyl‐N‐ser‐asp‐lys‐pro derived from thymosin β4 in neoplastic diseases

Abstract: The natural tetrapeptide acetyl-ser-asp-lys-pro (AcSDKP) is formed in vivo by enzymatic cleavage of the N terminus of thymosin beta4 by prolyl oligopeptidase (POP). Recently, AcSDKP was shown to promote angiogenesis. Because of the critical role of neovascularization in cancer development, the levels of AcSDKP and POP activity in a number of different malignant tissues were investigated. Our studies revealed that AcSDKP levels were markedly elevated in neoplastic diseases including hematologic malignancies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…However the precise role that ACSDKP serves in leukemia has not yet been elucidated. It was identified that ACSDKP expression is upregulated in human leukemia (17) and it was demonstrated that ACSDKP could enhance the proliferation of U87-MG glioblastoma cells via the PI3KCA/Akt signaling pathway (20). Therefore, the current study aimed to determine the role of ACSDKP in AML.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However the precise role that ACSDKP serves in leukemia has not yet been elucidated. It was identified that ACSDKP expression is upregulated in human leukemia (17) and it was demonstrated that ACSDKP could enhance the proliferation of U87-MG glioblastoma cells via the PI3KCA/Akt signaling pathway (20). Therefore, the current study aimed to determine the role of ACSDKP in AML.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that ACSDKP is associated with endothelial cell proliferation (13), the promotion of angiogenesis (14) and the inhibition of myofibroblast differentiation (15). ACSDKP is also considered to be abnormally expressed in some human malignant tumors, including tumors of the thyroid gland (16), breast, colon, head and neck, kidney, lung, skin, ovary and prostate (17,18). It has been demonstrated that ACSDKP expression varies during chemotherapy to treat patients with AML, in certain patients the ACSDKP level increased sharply during treatment, whereas in others it did not change or decreased (19); however, few studies investigating ACSDKP have been conducted since.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the details of the endogenous AcSDKP production pathway are not yet clear, the available evidence suggests that thymosin b4 (Tb4) is the most likely candidate precursor of AcSDKP. 130,131 AcSDKP is the N-terminal sequence of Tb4. Prolyl oligopeptidase may be responsible for the formation of AcSDKP, and prolyl oligopeptidase inhibitors may block the formation of AcSDKP from Tb4.…”
Section: Perspective: Anti-fibrosis Therapymentioning
confidence: 99%
“…We previously reported that Ac-SDKP decreased cardiac and renal inflammatory cell infiltration in various models of hypertension, as well as in the model of heart failure after myocardial infarction (27,28,33). In addition, Lin et al (14) demonstrated that Ac-SDKP prevented macrophage infiltration in the aorta in rats with angiotensin II (Ang II)-induced hypertension, and it suppressed ICAM-1 mRNA that is often used as a marker of endothelial cell inflammatory response (15). Furthermore, Nakagawa et al (22) showed that Ac-SDKP reduced ICAM-1 protein expression in experimental autoimmune myocarditis (EAM) (22).…”
mentioning
confidence: 99%